Properties and Applications of Bacterial Cellulose as a Biological Non-woven Fabric - Ashjaran, A. (Asian Journal of Chemistry, 2012)
The role of microbial technologies in utilization of the new raw material resources for fabrication of fibers, nonwoven fabric and films, in improving production of existing types of fibers and in creating new types of fiber materials of natural origin was evaluated. The potential capacity of microorganisms to form fiber structures, fiber and film forming polymers and the monomers for their chemical synthesis was analyzed. Nanofibers and biononwoven fabric of pure cellulose can be made from some bacteria such as Acetobacter xylinum. Bacterial cellulose fibers are pure, tens of nm across and about 0.5 μ long. The fibers are very stiff and, although nobody seems to have measured the strength of individual fibers. Their stiffness up to 70 GPa. Fundamental strengths should be at least greater than those of the best commercial polymers, but best bulk strength seems to about the same as that of steel. They can potentially be produced in industrial quantities at lowered cost and water content and with triple the yield, by a new process. This article presents a critical review of the available information on the bacterial cellulose as a biological nonwoven fabric with special emphasis on its fermentative production and applications. Characteristics of bacterial cellulose biofabric with respect to its structure and physicochemical properties are discussed. Current and potential applications of bacterial cellulose in textile, nonwoven cloth, paper, films synthetic fiber coating, food, pharmaceutical and other industries are also presented.